MAJOR BIOACTIVE PROPERTIES OF GANODERMA POLYSACCHARIDES: A REVIEW - AHMAD BHAT, ZAHOOR; HAMID WANI, ABDUL; WAR, JOHN MOHD; BHAT, MOHD YAQUB (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Ganoderma a white rot fungus has been used as a folk remedy for promoting health and longevity for centuries. The vast amount of study has been performed on the medicinal properties of Ganoderma in general and Ganoderma lucidum in particular. The bioactivities of the metabolites reported from G. lucidum are immense. The main bioactive metabolites of G. lucidum consist of mainly polysaccharides and triterpenoids. The major bioactive polysaccharides isolated from Ganoderma species are β (1→3), β (1→4), and β (1→6)-D glucans. With respect to the pure chemical and structural points of view, G. lucidum polysaccharides are mostly composed of β-glucans, heteropolysaccharides, and glycoptoteins. The major component of this sugar molecule is glucose together with xylose, mannose, galactose, and fructose in different conformations. Many of these bioactive polysaccharides have shown activities against the major diseases of our time and the list of effects shown is huge. Various important bioactivities, namely, antitumor, antioxidant, cytotoxic, immunomodulatory, antibacterial, anti-inflammation, neuroprotective, hepatoprotective, anti-HIV, and so on have been shown by these bioactive polysaccharides. The main purpose of this review is to report the most bioactive polysaccharides from G. lucidum and other species of Ganoderma and to report their potential health benefits.